2008
DOI: 10.1152/ajpendo.90253.2008
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of muscle protein synthesis by somatotropin in pigs is independent of the somatotropin-induced increase in circulating insulin

Abstract: Chronic treatment of growing pigs with porcine somatotropin (pST) promotes protein synthesis and doubles postprandial levels of insulin, a hormone that stimulates translation initiation. This study aimed to determine whether the pST-induced increase in skeletal muscle protein synthesis was mediated through an insulin-induced stimulation of translation initiation. After 7-10 days of pST (150 microg x kg(-1) x day(-1)) or control saline treatment, pancreatic glucose-amino acid clamps were performed in overnight-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
(104 reference statements)
1
3
0
Order By: Relevance
“…This is consistent with previous data in neonatal pigs where increasing either insulin or amino acids independently increased rates of muscle protein synthesis to levels associated with feeding, whereas increasing both insulin and amino acids to fed levels showed no additional stimulation (12). In a recent study (52), we demonstrated using pancreatic-glucose-amino acid clamps that rates of muscle protein synthesis were not further increased by raising circulating concentrations of insulin from fed untreated levels (25 U/ml) to plasma insulin levels seen in fed pST-treated animals (50 U/ml) when pigs are treated with pST (52). Taken together, it appears that the pST-induced increase in circulating insulin concentrations does not mediate the pST-induced increase in muscle protein synthesis, but fed amino acids are required for the pST-induced increase in muscle protein synthesis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with previous data in neonatal pigs where increasing either insulin or amino acids independently increased rates of muscle protein synthesis to levels associated with feeding, whereas increasing both insulin and amino acids to fed levels showed no additional stimulation (12). In a recent study (52), we demonstrated using pancreatic-glucose-amino acid clamps that rates of muscle protein synthesis were not further increased by raising circulating concentrations of insulin from fed untreated levels (25 U/ml) to plasma insulin levels seen in fed pST-treated animals (50 U/ml) when pigs are treated with pST (52). Taken together, it appears that the pST-induced increase in circulating insulin concentrations does not mediate the pST-induced increase in muscle protein synthesis, but fed amino acids are required for the pST-induced increase in muscle protein synthesis.…”
Section: Discussionsupporting
confidence: 93%
“…Although the increase in circulating glucose and insulin levels with pST treatment has been attributed to insulin resistance (28,53), kinetic studies indicate that reduced insulin-stimulated glucose uptake occurs in adipose tissue, not skeletal muscle (17,53). Even though insulin is known to promote skeletal muscle protein synthesis in a dose-dependent manner (38), we have demonstrated, by using pancreatic-glucose-aminoacid clamps, that the pST-induced increase in muscle protein synthesis is not due to the pST-induced increase in insulin concentration (52). We postulated that the inability of increased circulating insulin levels to further enhance rates of protein synthesis in the skeletal muscle of pST-treated pigs might be a consequence of the limited amino acid supply induced by maintaining amino acids at fasting concentrations.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Research using animal models has robustly demonstrated that GH administration increases net protein accretion in skeletal muscle by increasing protein synthesis 5 6 14 15 . GH administration stimulates endogenous production of insulin-like growth factor 1 (IGF-1; predominantly in the liver), which is considered at least partly accountable for the anabolic effects of GH 16 17 18 .…”
mentioning
confidence: 99%